USAID & CCAFS webinar: Making trees count: MRV for agroforestry under UNFCCC - Rosenstock, Todd S.; Tenneson, Karis; Cardinael, Rémi; Suber, Marta; Mulia, Rachmat; Patterson, Matthew; Bogle, Seth; Thanh, Pham Van; Daniel, James; Phuong, Nguyen Mai; Tan, Nguyen Quang; Arango, Jacobo; et al. (United State Agency of International Development (USAID) and CGIAR Research Program on Climate Change and Food Security (CCAFS), 2019)
Agenda Agroforestry for Livelihoods and Climate - Todd Rosenstock, ICRAF User friendly and cost-effective approach to identifying agroforestry: example from Southeast Asia - Karis Tenneson, SIG Revised Tier 1 carbon stock change factors for agroforestry: A critical step for improved MRV and national GHG reporting - Rémi Cardinael, CIRAD Overcoming barriers through intergovernmental dialogue on silvopastoral systems in Latin America - Marta Suber, ICRAF